2005
DOI: 10.1002/ange.200501495
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability and Ultrasmall‐Size Effect of Nanodiamonds

Abstract: Im Größenbereich unter 3 nm sind Nanodiamanten stabiler als Graphit. Experimentelle und theoretische Studien belegen nun, dass der pyhsikalische Ursprung für dieses Vehalten in der Oberflächenkrümmung der Nanodiamanten zu suchen ist. Ein ähnlicher Größeneffekt wurde für die Schrumpfung von Nanokavitäten bei Ionenbestrahlung beobachtet (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…These results 20,21 have been confirmed by other groups. X-ray diffraction and TEM studies 24,25 showed that NDPs ( d ∼ 5 nm) under thermal treatment at temperatures below 1973 K convert into spherical onion-like particles, having nearly the same size as the starting nanodiamond particles. At higher temperatures (∼2273 K), notably larger size hollow polyhedral particles are formed as the main product.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…These results 20,21 have been confirmed by other groups. X-ray diffraction and TEM studies 24,25 showed that NDPs ( d ∼ 5 nm) under thermal treatment at temperatures below 1973 K convert into spherical onion-like particles, having nearly the same size as the starting nanodiamond particles. At higher temperatures (∼2273 K), notably larger size hollow polyhedral particles are formed as the main product.…”
Section: Introductionsupporting
confidence: 54%
“…Unlike theoretical studies, the experimental work on interconversions of different nanoscale forms of carbon was carried out thus far mostly on diamond and onions. It involved either thermal stability studies of different size fractions or stability of the nanoparticles under high-energy electron 28 or laser 30 irradiation and did not particularly focus on size-dependent phase stability of these carbon forms.…”
Section: Introductionmentioning
confidence: 99%
“…A key aspect of this argument, independent of the specifics of the model, is that for a small-diameter wire a capillary pressure (or so-called Young-Laplace pressure) ΔP ≈ 2γ/r (where r is the radius) can be sufficiently high to allow the diamond phase to exist in the inner core while the outer shell with less equivalent pressure takes on the graphitic phase. Depending on the specific surface and interface energy parameters, within a thick nanotube-like shell of an interior radius around 10-25 nm, or for even smaller dimensions occurring at a defective spot of the nanotube wall, the equivalent pressure could reach the order of 1~5 GPa [17]. Similar phenomena were observed experimentally in diamond nucleation inside carbon onion high curvature enclosures [18].…”
Section: Status Of Effortsupporting
confidence: 66%
“…These observations were rationalized by surface energy measurements to yield phase diagrams comprising enthalpy as a function surface area (particle size), which revealed cross overs in stability below about 200 nm [139,140]. The oxides ZrO 2 [141] and Al 2 O 3 [142] also exhibit similar particle size-dependent phase stability, as does carbon for which nanodiamonds are more stable than graphite [143]. Molecular simulations have played a key role in predicting phase stability switch-overs for these inorganic oxides and in rationalizing observed experimental data, for example, see surface energy calculations on Al 2 O 3 [144].…”
Section: Phase Stability and Transitions At The Nanoscalementioning
confidence: 99%